Hubungan Media Sosial dengan Pertumbuhan Iman Remaja - Hita Bolo; Marsi Bombongan Rantesalu; Sance Mariana Tameon; Melly P Dethan (Institut Agama Kristen Negeri Kupang, 2024)
The aim of this research is to find out whether there is a relationship between social media and the growth of teenagers' faith. To achieve the results of this research, quantitative methods were used by collecting data through filling out questionnaires and testing the data using SPSS. Meanwhile, the data source came from 45 respondents from teenagers in the GBI Rehobot-Wekiar congregation. Social media is a tool or intermediary used to interact and communicate between someone and other people who provide many contributions or benefits. The growth of faith is a person's spiritual maturity which continues to grow towards perfection in Jesus Christ, has a different life from people who do not believe and becomes stronger in their faith in Jesus Christ. The research results illustrate that there is a significant relationship between variable X (Social Media) and variable Y (Faith Growth) of 0.001 < 0.05.